Proteomic profiling of the interface between the stomach wall and the pancreas in dystrophinopathy - Paul Dowling; Stephen Gargan; Margit Zweyer; Hemmen Sabir; Michael Henry; Paula Meleady; Dieter Swandulla; Kay Ohlendieck (PAGEPress Publications, 2021)
The neuromuscular disorder Duchenne muscular dystrophy is a multi-systemic disease that is caused by a primary abnormality in the X-chromosomal Dmd gene. Although progressive skeletal muscle wasting and cardio-respiratory complications are the most serious symptoms that are directly linked to the almost complete loss of the membrane cytoskeletal protein dystrophin, dystrophic patients also suffer from gastrointestinal dysfunction. In order to determine whether proteome-wide changes potentially occur in the gastrointestinal system due to dystrophin deficiency, total tissue extracts from the interface between the stomach wall and the pancreas of the mdx-4cv model of dystrophinopathy were analysed by mass spectrometry. Following the proteomic establishment of both smooth muscle markers of the gastrointestinal system and key enzymes of the pancreas, core members of the dystrophin-glycoprotein complex, including dystrophin, dystroglycans, sarcoglycans, dystrobrevins and syntrophins were identified in this tissue preparation. Comparative proteomics revealed a drastic reduction in dystrophin, sarcoglycan, dystroglycan, laminin, titin and filamin suggesting loss of cytoskeletal integrity in mdx-4cv smooth muscles. A concomitant increase in various mitochondrial enzymes is indicative of metabolic disturbances. These findings agree with abnormal gastrointestinal function in dystrophinopathy.